Waterbirds: an important bio-indicator of ecosystem - Abdul Rahman, Mohd Faid; Ismail, Ahmad (Universiti Putra Malaysia Press, 2018)
Waterbirds serve as an important bio-indicator of ecosystem changes and have been used widely throughout the world. This is because they exhibit conspicuous and meaningful responses to the changes of the environment around them. Other qualities that make them a good bio-indicator are also highlighted. Thus, important information on their biology and ecology are essential to make informed decisions. This is crucial in order to better conserve them and their habitats. Currently they are facing new challenges that arise from continuous development throughout the world. In addition, many endangered species continue to declines and could be extinct if they are not protected and conserved. The development of artificial habitat such as wetlands to compensate natural habitat loss could be an alternative. However, detailed information on the waterbirds and their interactions with the new environment are needed in order to do so. It is further highlighted that few researches have been conducted and focused on the waterbirds particularly in Malaysia. Thus, we encourage more local young scientists to take up this challenge and equip themselves with the right knowledge and necessary skills as well as to remain relevant with the international research standards. Proper planning, funding and focus should also be considered by the government and local authorities to maximize the impact of the country’s conservation effort.